M. C. Higgins, the great. - Hamilton, Virginia, 1936-2002. (New York : Macmillan, 1974)
As a slag heap, the result of strip mining, creeps closer to his house in the Ohio hills, fifteen-year-old M. C. is torn between trying to get his family away and fighting for the home they love.
Elem. School Library Collection.
Newbery Medal/Honor.
Wilson's Children.
Booklist, June 2003.
Elem. School Library Collection, March 1998.
Kirkus Review, November 2004.
Keywords: African Americans -- Fiction; Family life -- Fiction; African Americans -- Fiction; Family life -- Fiction